CP-046 An assessment of preference of visual and manual compliance aids. (25th February 2017) - Pavkovic, I; Bates, I; Coleman, B
Abstract : Background: Various studies have recommended that skills to assess safe self-medication management should be incorporated into routine evaluation of elderly patients. As seen in previous studies, pharmacists are more likely than other healthcare professionals to discover barriers to adherence to medication regimens among elderly patients and to undertake interventions to remove these barriers. Purpose: The aim was to investigate the issues of supporting those with impaired vision and manual dexterity in independently managing their medicines. Objectives of the study were to develop a screening tool to investigate impaired vision and manual dexterity in the elderly hospital inpatient population, to identify the prevalence of impaired vision and manual dexterity in an elderly hospital inpatient population and to determine patient perspectives of compliance aids to support manual and vision impaired patients. Material and methods: For this prospective, non-randomised, observational study, 18 consenting elderly patients were interviewed and given a choice of suitable compliance aids that could help them with their medication management. The patient's preference for a suitable compliance aid was recorded. Results: 18 of 459 patients (3.92%) on four wards were identified as having visual impairments and/or manual dexterity issues, that had an impact on their ability to self-administer medication. The majority of the study population was predominantly women (83.33%), with an overall mean age of 82±7 years. 77.8% of patients with visual impairment reported difficulty reading medication labels, despite using optical aids. 61.11% of patients that displayed manual dexterity issues stated their preferences for a compliance aid suitable to their impairment. Conclusion: Elderly inpatients in this study had impairments of their ability to self-administer their medication. By using a screening tool and suitable compliance aids, the pharmacist was able to detect adherence difficulties and their prevalence among the elderly inpatient population. Preference for a suitable compliance aid depended on the type of medications used. References and/or acknowledgements: Billups SJ, Malone DC, Carter BL. The relationship between drug therapy noncompliance and patient characteristics, health-related quality of life, and health care costs. Pharmacotherapy2000;20:941–9. Hurd PD, Butkovich SL. Compliance problems and the older patient: assessing functional limitations. Drug Intell Clin Pharm1986;20:228–31. No conflict of interest